Probing The Relation Between Vitamin D Deficiency and Progression of Medial Femoro-tibial Osteoarthitis of the Knee - Bassiouni, Hassan; Aly1, Hany; Zaky, Khaled; Abaza, Nouran; Bardin, Thomas (Current Rheumatology Reviews, 2017)
Objective: To compare serum 25 OH vitamin D (25 (OH) D) levels between medial femoro-tibial knee osteoarthritis (OA) patients and controls, and to detect structural progression in patients with mild to moderate knee osteoarthritis in relation to baseline 25(OH) D levels in a oneyear longitudinal prospective cohort study. Methods: Thirty eight patients with medial femoro-tibial knee OA according to the ACR criteria and no knee malalignement, and 20 age, sex and BMI-matched pain free controls were included in the vitamin D study. All included OA patients had radiographic Kellgren and Lawrence grades 2 or 3. Baseline serum levels of 25(OH) D, and the “Benefiting from ultraviolet index “(BFUI) score were determined; serum parathormone, total alkaline phosphatase, calcium and phosphorus were measured. In the OA progression study, OA patients were divided into 2 groups according to 25 (OH) D level using a cutoff of 10 ng/ml to identify their status. MRIs were done at baseline and repeated after 12 months with scoring system according to Boston Leeds osteoarthritis knee score (BLOKS). During the study period, the patients were not supplemented with 25(OH)D. Results: The mean values of Vitamin D were statistically lower in the OA patient group than in controls (8.64 ± 6.42 vs. 14.84±0.87 pg/mL, P =0.0295). The BFUI score overall correlated with 25 (OH) D status. Eight patients did not complete the study so only thirty OA patients underwent the 2 MRIs. Of those, 21 had 25(OH) D levels <10 ng/ml, while 9 had levels >10 ng/ml. A significant progression of the medial meniscal grading from baseline to 1 year was seen in the patients with 25(OH)D levels <10 ng/ml as compared to the others (Wilcoxon Z= -3.556 P<0.001). Conclusion: 25 (OH) D levels were significantly decreased in knee OA patients. Significant deterioration of the medial menisci was observed in OA patients with 25 (OH)D levels <10 ng/ml suggesting that Vit D deficiency may play a role in the progression of medial femoro-tibial OA.
Keywords: BLOKS score